A local landscape in transition between production and consumption goals: can new management arrangements preserve the local landscape character?. Issue 1 (2nd January 2016) - Pinto-Correia, Teresa; Almeida, Mara; Gonzalez, Carla
Abstract: Around towns in the Alentejo region, the landscape is dominated by a characteristic agricultural small-scale mosaic. These areas are central in the region landscape character – even if the large-scale latifundia landscape of the extensive silvo-pastoral systems is most commonly associated with the region. In the last two decades, these parcels became extremely attractive for new comers, who settle in the rural context as residents, week-end visitors, being often also lifestyle farmers. The paper presents a case study landscape, in Montemor-o-Novo, a small town 100 km from Lisbon, highly subject to the pressure for consumption uses, by urban users. The study shows that the new owners, even if they have settled in the area due to the tranquility and social bindings of the rural, end up doing farming, with new or reshaped production objectives, markets and models, but at the same time maintaining the traditional farm systems. Thus, the landscape character is maintained, so far. Nevertheless, the role of these neo-rurals and lifestyle farmers is still an unseen role, both by the agriculture and the planning sectors. And thus the question is, whether the combination of actors and land management drivers will continue maintaining the landscape in the future.